Is Uruguay More Resilient This Time? Distributional Impacts of a Crisis Similar to the 2001/02 Argentine Crisis - Cabanillas, Oscar Barriga; Lugo, Maria Ana; Nielsen, Hannah; Rodriguez Castelan, Carlos; Zanetti, Maria Pia (World Bank, Washington, DC, 2014)
The 2001/02 Argentine crisis had a profound impact on Uruguay's economy. Uruguay's gross domestic product shrank by 17.5 percent and the proportion of people living below the poverty line doubled in just two years. It took almost 10 years for the poverty rate to recover to its pre-crisis level. This paper uses a macro-micro simulation technique to simulate the impact of a similar crisis on the current Uruguayan economy. The simulation exercise suggests that Uruguay would now be in a better place to weather such a severe crisis. The impact on poverty would be considerably lower, inequality would not change significantly, and household incomes would be 8 percent lower than in the absence of a crisis (almost 9 percent lower for those households in the bottom 40 percent of the income distribution). Young individuals, female-headed households, those living in Montevideo, and those who do not have complete secondary education are more vulnerable to falling into poverty were the crisis to strike.